Design and analysis of a climbing robot for weld detection. Issue 1 (1st November 2022) - Li, Zhongqin; Fan, Jiaqing
Abstract: The climbing robot is gradually applied to the safety weld detection on large metal walls to avoid manual operation. However, most robots are difficult to perform efficient operations for the poor performance on obstacle overcoming, flexible turning and motion stability. This paper presents a weld detection climbing robot, which integrates contact permanent magnet adsorption units and crawler chain mobile mechanism to obtain continuous, flexible and stable motion performance on large metal walls. By establishing the robot mechanical model, the minimum adsorption force can be calculated considering the instability conditions such as sliding, longitudinal overturning and lateral overturning. Combined with the Ansys Maxwell simulation, the magnet structure was optimized to obtain the structural size of a single permanent magnet adsorption unit. Experimental results show the robot can achieve stable motion and accurate detection on large metal walls with welds, and the maximum load of the robot can reach to 15.6 kg, which meets the engineering application requirements of weld detection on large metal walls.